2018
DOI: 10.1371/journal.pone.0206663
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of failed intrauterine balloon tamponade for persistent postpartum hemorrhage after vaginal delivery

Abstract: ObjectiveTo identify the predictors of intrauterine balloon tamponade (IUBT) failure for persistent postpartum hemorrhage (PPH) after vaginal delivery.DesignRetrospective case-series in five maternity units in a perinatal network.SettingAll women who underwent IUBT for persistent PPH after vaginal delivery from January 2011 to December 2015 in these hospitals.MethodsAll maternity apply the same management policy for PPH. IUBT, using a Bakri balloon, was used as a second line therapy for persistent PPH after fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
0
14
0
1
Order By: Relevance
“…Women with persistent postpartum hemorrhage may develop coagulopathy with blood loss, dilution, and consumption of platelets and coagulation factors, requiring high rates of blood transfusions. Previous studies have shown that EBL before IUBT is associated with IUBT failure (8,11,20), with an odds ratio for EBL before IUBT (>1,500 ml) of 3.2 (8). Howard and Grobman (21) reported that women receiving IUBT at higher EBL quartiles had more frequent packed red blood cell transfusions and more hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…Women with persistent postpartum hemorrhage may develop coagulopathy with blood loss, dilution, and consumption of platelets and coagulation factors, requiring high rates of blood transfusions. Previous studies have shown that EBL before IUBT is associated with IUBT failure (8,11,20), with an odds ratio for EBL before IUBT (>1,500 ml) of 3.2 (8). Howard and Grobman (21) reported that women receiving IUBT at higher EBL quartiles had more frequent packed red blood cell transfusions and more hysterectomies.…”
Section: Discussionmentioning
confidence: 99%
“…The initial screening identified 43 articles as duplicates, letters, or editorials or as unrelated to the management of PPH with BBT. Of a total of 90 studies that were retrieved to assess eligibility, five were selected as relevant [ 20 , 21 , 22 , 23 , 24 ]. A flowchart for study selection is presented in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The most common cause of PPH was uterine atony (50%), followed by placenta previa (28.1%). Two studies only included patients with placenta previa and caesarean delivery (21–22), and 1 study that only included patients with vaginal delivery [ 24 ]. The global success rate for BBT was 79.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, Grange et al examined the predictors of failed IUBT for persistent PPH after vaginal delivery (25). They reported that body mass index, labour duration, estimated blood loss and more than four packed of erythrocyte transfusion were statistically significant in predicting the failure of IUBT.…”
Section: Discussionmentioning
confidence: 99%